"An old man's eagle mind": A Passionate Refashioning of the Poet's Self in W. B. Yeats's 'An Acre of Grass' (Global Journal of Human-Social Science, 2021)
Yeats's Last Poems (1939), according to critics like F. R. Leavis, lacks the complexity and tension of his earlier works. Instead, most of the poems included in this collection are evocative of the mood of resignation and the decrepitude of old age. Amidst this physical decay, the poetic persona relentlessly strives to refashion the 'self' by transmuting his passion into creative energy. The realization of truth regarding the tragic gaiety of the mind heightens the psychological tension arising from the conflict between the body and the soul. The poetic refashioning is informed by the persistence of the creative impulse that contributes to the integrity of the 'self' and its symbolic defiance of the ineluctable physical process. Taking Yeats's poem, 'An Acre of Grass', as the case study, this paper would examine how the process of poetic composition corresponds to the cycle of human existence -birth, decay, and rebirth.
Keywords: physical decay; passion; creative energy; transmute; self; refashion